Oprah Winfrey : the life of a media superstar - Jeffrey, Gary.; Riley, Terry (New York : Rosen, 2007)
A brief profile, written in graphic comic format, of the life and achievements of daytime talk show host Opra Winfrey.
Includes bibliographical references (p. 47) and index.
5.6
5-8
Keywords: Winfrey, Oprah -- Comic books, strips, etc. -- Juvenile literature; Winfrey, Oprah -- Cartoons and comics; Winfrey, Oprah -- Comic books, strips, etc; Actors -- United States -- Comic books, strips, etc. -- Juvenile literature; Television personalities -- United States -- Comic books, strips, etc. -- Juvenile literature; Actors and actresses -- Cartoons and comics; African Americans -- Cartoons and comics; Cartoons and comics; Television personalities -- Cartoons and comics; Women -- Cartoons and comics; Actors -- United States -- Comic books, strips, etc; African Americans -- Comic books, strips, etc; Comic books, strips, etc; Television personalities -- United States -- Comic books, strips, etc; Women -- Comic books, strips, etc